Betriebsräte ohne Gewerkschaften? Zur Praxis und Problematik der Erosion eines Kooperationsverhältnisses - Artus, Ingrid; Röbenack, Silke (Industrielle Beziehungen - Zeitschrift für Arbeit, Organisation und Management, 2021)
A functional division of labor that involves close cooperation between works councils and trade unions is important for the stability of the overall system of German industrial relations. However, although works councils and trade unions often work closely together erosive tendencies can be observed in this cooperative relationship. The text uses empirical data to analyze the practices and problems of co-determination work that is only loosely connected or completely disconnected from trade union policies. We provide a historical overview as well as a current analysis of the state of relations between works councils and trade unions. Based on qualitative case studies in 35 companies, patterns and problems of non-union codetermination practices are presented. Finally, the effects of non-union co-determination policies on the overall system of industrial relations are discussed, as well as the possibilities for union and political intervention.
CRIS-Team Scopus Importer:2024-12-16
Keywords: co-determination; JEL: J50; J51; J52; J59; M14; trade unions; Works councils; Betriebsräte; Gewerkschaften; betriebliche Mitbestimmungspraxis